Performance characteristics of soot primary particle size measurements by time-resolved laser-induced incandescence. - Will, Stefan; Schraml, Stephan; Bader, Katharina; Leipertz, Alfred (Applied Optics, 1998)
A detailed analysis of various factors that influence the accuracy of time-resolved laser-induced incandescence for the determination of primary soot particles is given. As the technique relies on the measurement of the signal ratio at two detection times of the enhanced thermal radiation after an intense laser pulse, guidelines are presented for a suitable choice of detection times to minimize statistical uncertainty. An error analysis is presented for the issues of laser energy absorption, vaporization, heat conduction, and signal detection. Results are shown for a laminar ethene diffusion flame that demonstrate that concurring results are obtained for various laser irradiances, detection characteristics, and times of observation.